A Case Study for Synthesis of Zeolite-A from Indian Flyashes of Bituminous Origin - Rayalu, S.S.; Sapre, J.S.; Meshram, S.U.; Munshi, K.N.; Singh, R.N. (Asian Journal of Chemistry, 2016)
Attempts were made to synthesise zeolites from flyash of different origins and elemental characteristics. Influence of elemental content especially SiO2, Al2O3, Fe2O3 and CaO has been studied in detail. The flyash investigated herein are both from bituminous coal but with different LOI content which seems to be detrimental for synthesis of zeolite-A from flyash. The physico-chemical characteristics of zeolites synthesised from flyash from Shriram Fertiliser Company Limited (FASBC) and flyash from Tamil Nadu Electricity Board (FATBC) are comparable with commercial zeolite-A.